EXPLORING THE IMPACT OF LEARNING FACILITIES AND ENVIRONMENT ON STUDENT MOTIVATION - Fanny, Putri Olivia; Faslah, Roni; Swaramarinda, Darma Rika (Faculty of Economics and Business, Universitas Negeri Jakarta, 2024)
Motivation for students is certainly high and low with various factors that influence the motivation. For students who have high learning motivation, they will devote all their attention to the ongoing learning. This study aims to analyze the effect of learning facilities and learning environment on the learning motivation of students of the Faculty of Economics, Jakarta State University. The population used in this study were all students of the Faculty of Economics, Jakarta State University, class of 2020 with a population of 633 students. This study uses a quantitative method, and a sample of 245 students was determined. The sampling technique used Proportional Sampling. Data collection was carried out by distributing questionnaires using a Likert scale. This study uses an analysis technique using SmartPLS 3.0 with Outer Model and Inner Model analysis. The research results show that (1) there is a significant influence between learning facilities and learning motivation, (2) there is a significant influence between the learning environment and learning motivation, and (3) there is a significant influence between learning facilities and the learning environment and learning motivation.